The Multifaceted Role of the Vasculature in Endochondral Fracture Repair - Bahney, Chelsea S.; Hu, Diane P.; Miclau, Theodore; Marcucio, Ralph S. (Frontiers in Endocrinology, 2015)
Fracture healing is critically dependent upon an adequate vascular supply. The normal rate for fracture delayed or non-union is estimated to be between 10-15%, and annual fracture numbers are approximately 15 million cases per year. However, when there is decreased vascular perfusion to the fracture, incidence of impaired healing rises dramatically to 46%. Reduction in the blood supply to the fracture can be the result of traumatic injuries that physically disrupt the vasculature and damage supportive soft tissue, the result of anatomical location (i.e. distal tibia), or attributed to physiological conditions such as age, diabetes or smoking. The role of the vasculature during repair is multifaceted and changes during the course of healing. In this article, we review recent insights into the role of the vasculature during fracture repair. Taken together these data highlight the need for an updated model for endochondral repair to facilitate improved therapeutic approaches to promote bone healing.